Development of Differentiated Learning Model Based on Gamification for Elementary School Children - Fajarianto, Otto; Wulandari, Dwi; Setiyowati, Arbin Janu; Ayunin, Qurrota; Maryam, Sinta Dewi; Ayunin, Salsabella Qurrota; Ismail, Affero (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
Differentiated learning is an effort to adapt the learning process to the learning needs of each student. Education in Indonesia, through the independent curriculum, is starting to introduce a lot of student-oriented learning. So there needs to be an appropriate learning approach that can be applied to learning activities. So the aim of this research is to evaluate previous scientific research articles related to differentiated learning in elementary schools (SD). In order to examine the usefulness of the differentiated learning approach in elementary schools (SD). In this article, the research method used is a literature review. The research data used are articles published within the last 5 years, namely between 2019 and 2023. As well as at the elementary school (SD) education level. This research stage was carried out by searching the literature with the keyword